Faktor Yang Mempengaruhi Keberhasilan Program Imunisasi Dasar di UPT Puskesmas Rappang - Nurul Ashira; Mardhatillah; Khaeriyah Adri (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2026)
Immunization Immunization is important for preventing infectious diseases and reducing child morbidity and mortality. In 2022, the coverage of complete basic immunization in Sidrap Regency was 68.3%, still below the national target of 95%. This study aimed to analyze the influence of mothers’ knowledge, vaccine availability, health workers’ competence, and access to health services on the success of basic immunization at UPT Puskesmas Rappang. This study used a quantitative approach with a cross-sectional design. The population consisted of 318 infants, with a sample of 177 respondents determined using the Slovin formula. Data were collected through questionnaires and documentation, then analyzed using logistic regression. The results showed that all variables had a significant effect on the success of basic immunization, both simultaneously and partially. The most dominant variable was the accessibility of health facilities. Therefore, the success of basic immunization is influenced by mothers’ knowledge, service quality, and ease of access to health services.